2014
DOI: 10.4049/jimmunol.1302411
|View full text |Cite
|
Sign up to set email alerts
|

PIKfyve, a Class III Lipid Kinase, Is Required for TLR-Induced Type I IFN Production via Modulation of ATF3

Abstract: Type I IFN plays a key role in antiviral responses. It also has been shown that deregulation of type I IFN expression following abnormal activation of TLRs contributes to the pathogenesis of systemic lupus erythematosus. In this study, we find that PIKfyve, a class III lipid kinase, is required for endolysosomal TLR-induced expression of type I IFN in mouse and human cells. PIKfyve binds to phosphatidylinositol 3-phosphate and synthesizes phosphatidylinositol 3,5-bisphosphate, and plays a critical role in endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…These findings are consistent with a recent study showing that TLR-induced type I IFN levels were reduced by a PIKfyve inhibitor in RAW264.7 murine macrophage cells via induction of ATF3 (21). Immune cells can rapidly respond to low systemic concentrations of type I IFNs, which are constitutively maintained under homeostatic conditions by the commensal microflora (48,49).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings are consistent with a recent study showing that TLR-induced type I IFN levels were reduced by a PIKfyve inhibitor in RAW264.7 murine macrophage cells via induction of ATF3 (21). Immune cells can rapidly respond to low systemic concentrations of type I IFNs, which are constitutively maintained under homeostatic conditions by the commensal microflora (48,49).…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, virus infection induces nucleosome remodeling of the Ifnb1 promoter (via histone acetyl transferases, as well as the SWI/SNF chromatin remodeling complex), allowing for increased transcription (56). Consistent with the role of ATF3 as a transcriptional repressor, two recent studies suggested that ATF3 has binding sites within the Ifnb1 promoter (21,30). Our ChIP-seq dataset (26) has identified an ATF3 binding site at a regulatory element 15 kbp upstream of the Ifnb1 TSS, which showed significant and specific enrichment of ATF3 under basal conditions (Fig.…”
Section: Isgs Similar To Atf3mentioning
confidence: 77%
See 1 more Smart Citation
“…Second, drug-treated mammalian cells retain small levels of PtdIns(3,5)P 2 that may suffice to maintain acidic lysosomes. Yet, at these low levels of PtdIns(3,5)P 2 , many other defects are observed including lysosome swelling, phagosome maturation arrest, cytokine production impairment, and trafficking inhibition (38,39,51). Third, we do not exclude the possibility that extremely enlarged lysosomes may be more prone to alkalinization, as suggested elsewhere (31).…”
Section: Discussionmentioning
confidence: 99%
“…Out of those 37 TFs predicted to regulate genes in the SLE pathway, we found literature support for 13 (or 35%). The TFs associated by REPA with SLE are the following (supporting literature is referred to after the corresponding TF): ATF2, ATF3 [46], BCLAF1, CBX3, CEBPB, CEBPD, ETS1 [47], FOS [45], FOXM1, GR [48], HEY1, INI1, JUND [49], MBD4 [50], MTA3, MYBL2, NFATC1 [49], NFIC, P300 [51], PAX5 [52], PML, POL2, POU2F2, RUNX3 [53], RXRA, SIN3AK20, SP1 [54], SP4, STAT5A, TAF1, TAF7, TBP [55], TCF12, TCF3, TEAD4, YY1 [56], and ZBTB33.…”
Section: Number Of Repa's Predictions Per Gene Setmentioning
confidence: 99%